High-order statistics based blind channel estimation for PSK modulation in flat and slow fading channels - IXiao-tian L; EIJing L; LIUWei ,; IYan-bin L; HANGRun-sheng Z (Tongxin xuebao)
A blind channel estimator based on high-order statistics (HOS) of PSK constellations was proposed.For flat and slow fading channels,firstly,the high-order statistics of PSK constellations with different alphabet size M was ana-lyzed.The Mth power symbols of MPSK constellations are same,whereas the Mthpower symbols are symmetrically dis-tributed on the complex plane when 1≤M′＜M.Secondly,the estimation algorithms of alphabet size M,initial phase and fading coefficient were introduced based on the characteristics above.Finally,simulation results show that when SNR＞12 dB,the proposed algorithm has the same estimation performance as the optimal Lloyd-Max algorithm,while the complexity is only 1/50 of Lloyd-Max algorithm.Moreover,the proposed algorithm's mean-square error curve converges remarkably to the least squares (LS) bound on the condition of less received symbols.